THE EFFECT OF SNOWBALL THROWING METHOD ON THE SPEAKING ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 1 KUNTO DARUSSALAM - Nurkhairani Nurkhairani; Effendy Gultom; Mahdum Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research is to know the effect of Snowball Throwing Method on the Speaking Ability of the Second Year Students of SMPN 1 Kunto Darussalam. This research was pre-experimental design involving 30 students as a sample chosen through cluster random sampling technique. The data were gained before and after the treatment implementing Snowball Throwing Method. The students were given pre-test and post-test. The average score for pre-test was 40.75 and the average score for post-test was 61.11. The data shows that there are an increass from the pre-test and the post-test. The data analysis shows that the t-test is higher than t-table (17.424> 2.045)at the significant level of 5%. Therefore, alternative hipothesis is accepted and null hipothesis is rejected. It can be concluded that there is a significant effect of Snowball Throwing Method on the Speaking Ability of the Second Year Students of SMPN 1 Kunto Darussalam.Keywords: Effect, Ability, Snowball Throwing.